2021
DOI: 10.26452/ijrps.v12i3.4773
|View full text |Cite
|
Sign up to set email alerts
|

In-vitro antioxidant and selective cytotoxicity of Garcinia cambogia and Garcinia indica leaf extracts on human kidney cancer cell line

Abstract: Kidney cancer is one among the top 10 cancers. Renal cell carcinoma (RCC) is commonly known kidney cancer. Almost all clinically targeted drugs used in treating RCC have many aftereffects. To overcome this problem with herbal products, the present study is aimed to investigate the preliminary phytochemicals, antioxidants and selective cytotoxicity of aqueous leaves extract of Garcinia cambogia (GC)and Garcinia indica  (GI)on(HEK-293) human embryonic kidney cells and (A498)human renal carcinoma cells. The phyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
1
1
Order By: Relevance
“…The main objective of cancer therapeutics is to target specifically malignant cells without destroying normal cells, that is the main limitation of chemotherapeutic drugs. In the present study, both plant extracts showed cytotoxicity against HepG2 cells without damaging the normal cells, while cisplatin (a platinum-based anticancer drug) induces an antitumor effect through apoptotic stimulation in cancer as well as in normal (non-cancerous) cells, these outcomes are inconsistent with the previous study 79 . So, this plant can potentially treat liver cancer without disturbing normal cells.…”
Section: Discussioncontrasting
confidence: 99%
“…The main objective of cancer therapeutics is to target specifically malignant cells without destroying normal cells, that is the main limitation of chemotherapeutic drugs. In the present study, both plant extracts showed cytotoxicity against HepG2 cells without damaging the normal cells, while cisplatin (a platinum-based anticancer drug) induces an antitumor effect through apoptotic stimulation in cancer as well as in normal (non-cancerous) cells, these outcomes are inconsistent with the previous study 79 . So, this plant can potentially treat liver cancer without disturbing normal cells.…”
Section: Discussioncontrasting
confidence: 99%
“…The TFC was determined to be 50.33 mg QUE/g, akin to the value of 52.56 mg QUE/g observed in the methanol extract of G. indica (Kunjiappan et al ., 2020). The IC 50 value for DPPH radical scavenging activity of the dehydrated G. indica rind was measured at 485.1 μg/mL which was lower than the values reported for G. cambogia were value was 493.7 μg/mL (Jayakar et al ., 2021). The TPC content was lower due to the change in polarity and similarly, the TFC content was higher due to polarity, chelating process and scavenging (Kumar et al ., 2023).…”
Section: Resultsmentioning
confidence: 99%
“…Plant extracts are the best sources to evaluate the anticancer activity with least or no side effects for safe diagnosis (50). The anticarcinogenic activity of B. tomentosa synthesized AgNPs was established by the MTT assay on lung A549 carcinoma cell line.…”
Section: Anticancer Activitymentioning
confidence: 99%